Mitral valve surgery: current status and future prospects of the minimally invasive approach. (4th March 2021) - Van Praet, Karel M.; Kempfert, Jörg; Jacobs, Stephan; Stamm, Christof; Akansel, Serdar; Kofler, Markus; Sündermann, Simon H.; Nazari Shafti, Timo Z.; Jakobs, Katharina; Holzendorf, Stefan; Unbehaun, Axel; Falk, Volkmar
ABSTRACT: Introduction : During the past five years the approach to procedural planning, operative techniques and perfusion strategies for minimally invasive mitral valve surgery (MIMVS) has evolved. With the goal to provide a maximum of patient safety the procedure has been modified according to individual patient characteristics and is largely based on preoperative imaging. Areas covered : In this review article we describe the important factors in image based therapy planning and simulation, different access strategies, the operative key-steps, a rationale use of devices, and highlight a few future developments in the field of MIMVS. Published studies were identified through pearl growing, citation chasing, a search of PubMed using the systematic review methods filter, and the authors' topic knowledge. Expert opinion : With the help of expert teams including surgeons specialized in mitral repair, anesthesiologists and perfusionists a broad spectrum of mitral valve pathologies and related pathologies can be treated with excellent functional outcomes. Avoiding procedure related complications is the key for success for any MIMVS program.